Interaction of BRAF-induced ETS factors with mutant TERT promoter in papillary thyroid cancer. Issue 6 (June 2019) - Song, Young Shin; Yoo, Seong-Keun; Kim, Hwan Hee; Jung, Gyeongseo; Oh, Ah-Reum; Cha, Ji-Young; Kim, Su-jin; Cho, Sun Wook; Lee, Kyu Eun; Seo, Jeong-Sun; Park, Young Joo
Abstract : Synergistic effects of BRAF V600E and TERT promoter mutations on the poor clinical outcomes in papillary thyroid cancer (PTC) have been demonstrated. The potential mechanism of this phenomenon has been proposed: MAPK pathway activation by the BRAF V600E mutation may upregulate E-twenty six (ETS) transcription factors, increasing TERT expression by binding to the ETS-binding site generated by the TERT promoter mutation; however, it has not yet been fully proven. This article provides transcriptomic insights into the interaction between BRAF V600E and TERT promoter mutations mediated by ETS factors in PTC. RNA sequencing data on 266 PTCs from The Cancer Genome Atlas and 65 PTCs from our institute were analyzed for gene expression changes and related molecular pathways, and the results of transcriptomic analyses were validated by in vitro experiments. TERT mRNA expression was increased by the coexistence of BRAF V600E and TERT promoter mutations (fold change, 16.17; q- value = 7.35 × 10 −12 vs no mutation). In the ETS family of transcription factors, ETV1, ETV4 and ETV5 were upregulated by the BRAF V600E /MAPK pathway activation. These BRAF V600E -induced ETS factors selectively bound to the mutant TERT promoter. The molecular pathways activated by BRAF V600E were further augmented by adding the TERT promoter mutation, and the pathways related to immune responses or adhesion molecules were upregulated by TERT expression. The mechanism of the synergistic effect between BRAF V600E and TERT promoter mutations on cancer invasiveness and progression in PTC may be explained by increased TERT expression, which may result from the BRAF -induced upregulation of several ETS transcription factors.